JOB SATISFACTION AND INTERPERSONAL RELATION: A DETERMINANT OF JOB PERFORMANCE OF ACADEMIC STAFF OF COLLEGES OF EDUCATION IN LAGOS STATE, NIGERIA - Lewis, Modupe Bosede; Olowo, Busuyi Francis; Okotoni, Comfort Abosede (International Journal of Indonesian Education and Teaching (IJIET), 2020)
This study investigated the influence of job satisfaction and interpersonal relations on job performance of academic staff of colleges of education in Lagos State. A quantitative approach with survey design was used for the study. Population for the study comprised 516 academic staff and 6042 students of all the colleges of education in Lagos State. Sample for the study comprised 51 lecturers and 604 students. The sample was selected using multistage sampling procedure. Two research instruments were used for the study. Data were analysed using percentage and ANOVA statistics at 0.05level of significance. The results showed that there was a high level of job satisfaction among the academic staff of the colleges of education in Lagos State (58%). The results also showed that there was a moderate level of interpersonal relations between the academic staff and the students (69.7%) and there was a moderate level of interpersonal relations between the staff and management of the institutions (48%). The study further showed that job satisfaction (F=3.026, df=20, 29, P > 0.05) and interpersonal relations (F=3.026, df = 20, 29, P > 0.05) had a positive significant influence on job performance of academic staff.Â  The study concluded that job satisfaction and interpersonal relations positively influenced job performance of academic staff of colleges of education in Lagos State.Corresponding author:Â Busuyi Francis OlowoDOI: 10.24071/ijiet.2020.040214